2019
DOI: 10.1101/531780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual airway and alveolar contributions to adult lung homeostasis and carcinogenesis

Abstract: Lung adenocarcinoma (LUAD) and chronic lung diseases caused by smoking and environmental noxious agents are the deadliest diseases worldwide, sharing a partially charted pathobiology of dysfunctional alveolar repair. Here we sought to identify the respiratory epithelial dynamics and molecular signatures participating in adult lung maintenance and chemical carcinogenesis. We employed novel mouse models of respiratory epithelial marking and ablation, a battery of pulmonary toxins and carcinogens, experimental pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Selective ablation of bronchiolar epithelial cells results in the loss of circadian clock oscillations in mouse lung slices, demonstrating that airway epithelial cells are key circadian oscillators within the lung (12). NSCLC is a cancer of epithelial origin (13,14), so this reinforces the hypothesis that disruption of the circadian machinery could trigger harmful events due to dysregulation of homeostasis, resulting in increased risk of lung tumor development.…”
Section: Introductionmentioning
confidence: 65%
“…Selective ablation of bronchiolar epithelial cells results in the loss of circadian clock oscillations in mouse lung slices, demonstrating that airway epithelial cells are key circadian oscillators within the lung (12). NSCLC is a cancer of epithelial origin (13,14), so this reinforces the hypothesis that disruption of the circadian machinery could trigger harmful events due to dysregulation of homeostasis, resulting in increased risk of lung tumor development.…”
Section: Introductionmentioning
confidence: 65%
“…[1][2][3] Lung adenocarcinoma has been postulated to originate from club cells, AT2 cells, or BASCs, while squamous cell carcinomas likely arise from basal cells. [4][5][6] Experimental models have shown that given different oncogenes, lung cells can be more or less "fit" to form fully malignant lesions. [7][8][9] However, the cellular origins for the majority of lung cancers have not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse studies suggest that club cells located at the terminal bronchioles serve as progenitor cells not only for airway cells but also for AT2like cells and are likely involved in regeneration of the lung after severe injury. Whether these club cells, which express AT2 markers, actually differentiate into true AT2 cells, or whether they have other, unknown functions in the regeneration and repair of the lung parenchyma after severe damage, is not completely understood [5][6][7][8][9]. Single cell analysis revealed that the human respiratory bronchioles also contain secretory airway epithelial cells that are able to differentiate into AT2 cells [10].…”
Section: Introductionmentioning
confidence: 99%